2015
DOI: 10.1097/inf.0000000000000879
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Human Rhinovirus Types and Viral Load on the Severity of Illness in Hospitalized Children With Lower Respiratory Tract Infections

Abstract: HRV was frequently present in hospitalized children with lower respiratory tract infections in Chongqing, China. The disease severity for HRV-C and HRV-A was similar. A high load of HRV-A in the lower respiratory tract might be connected with disease severity in children younger than 2 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 34 publications
5
23
1
3
Order By: Relevance
“…In comparison, other reports on the quantification of HRV used only consensus RT-qPCR assays, quantified from standard curves generated from a single HRV genotype, and tested a limited number of HRV genotypes (14)(15)(16). Nevertheless, our findings confirm the results from some of these studies and show that assay quantification ability is linked to target variability and that accurate HRV quantification by a single RT-qPCR assay is not feasible for all HRV genotypes (17,18).…”
Section: Discussionsupporting
confidence: 80%
“…In comparison, other reports on the quantification of HRV used only consensus RT-qPCR assays, quantified from standard curves generated from a single HRV genotype, and tested a limited number of HRV genotypes (14)(15)(16). Nevertheless, our findings confirm the results from some of these studies and show that assay quantification ability is linked to target variability and that accurate HRV quantification by a single RT-qPCR assay is not feasible for all HRV genotypes (17,18).…”
Section: Discussionsupporting
confidence: 80%
“…HRV‐C accounts for the majority of asthma attacks in children and causes more severe attacks than other HRV types and other viruses . In our previous study, we found that HRV infection was associated with asthma in our region . Some authors have demonstrated a close correlation between the HRV viral load and the disease severity in children with lower respiratory tract infections .…”
Section: Introductionsupporting
confidence: 47%
“…Interpersonal variability and the unpredictable nature of respiratory viral infections pose a challenge to surveillance and preparedness programs [175]. Influenza seasons in particular vary with respect to case numbers and disease severity attributable to various viral subtypes and population strata [67,68,113,127]. The prospective monitoring of disease severity associated with laboratory-confirmed diagnoses will help to delineate vulnerable subpopulations expressing disease severity differently compared to the population average.…”
Section: Discussionmentioning
confidence: 99%